The effect of Zingiber officinales active compounds against microfilariae Brugia malayi in Fells catus, L. - Budi Mulyaningsih, Budi Mulyaningsih (Universitas Gadjah Mada, 1995)
Zingiber officinale, Rosa is a well known plant which can be used for the treatment of various diseases, and has been reported as an effective medicinal plant against Dirofilaria immitis in animal. The volatile oil and the pungent of Zingiber officinale, Rosa have been effectively used against larvae stage 3 (L3) B. malayi in vitro study.This study was designed to investigate the effect of the volatile oil and the pungent of Zingiber officinale, Rosc. against microfilariae B. malayi in Fells catus, L..Antifilarial activity of the pungent compound (isolate 1) and the volatile oil were assayed in vivo.The results showed that the volatile oil had the most quantity (rendement 0,5 %) and its activity against microfilariae B. malayi was higher than that of isolate 1, but lower thanÂ that of the dietylacarbamasine drug.Key words: microfilariae - volatile oil - the pungent of medicinal plant - B. malayi - Felis caws L